2013
DOI: 10.1111/hae.12175
|View full text |Cite
|
Sign up to set email alerts
|

Rapid musculoskeletal ultrasound for painful episodes in adult haemophilia patients

Abstract: Little objective information exists about musculoskeletal bleeding patterns in haemophilic arthropathy. Bleeding is assumed to be the cause of painful joints or muscles. Clotting factor treatment is provided empirically, but often does not alleviate pain. We hypothesized that perception of pain aetiology is unreliable, and introduced point-of-care high-resolution musculoskeletal ultrasound (MSKUS) to differentiate intra-articular bleeds vs. joint inflammation, and intra-muscle bleeds vs. other regional pain sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
196
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(204 citation statements)
references
References 20 publications
4
196
1
2
Order By: Relevance
“…Another explanation could be that symptoms of hemophilic arthropathy, such as pain, swelling, and stiffness, may have been perceived as bleeding episodes, and therefore treated as such, even though no bleeding episode had actually occurred. 24 The results presented here demonstrate wide interpatient variability, and this unexpected finding requires further investigation.…”
Section: Org Frommentioning
confidence: 62%
“…Another explanation could be that symptoms of hemophilic arthropathy, such as pain, swelling, and stiffness, may have been perceived as bleeding episodes, and therefore treated as such, even though no bleeding episode had actually occurred. 24 The results presented here demonstrate wide interpatient variability, and this unexpected finding requires further investigation.…”
Section: Org Frommentioning
confidence: 62%
“…This prompted investigation into alternative new imaging modalities, which led to the adoption of musculoskeletal ultrasound (MSKUS) for the imaging of hemophilic joints and its recent introduction into clinical practice. 25–28 Continued innovative development and wide-spread utilization for HA care are expected over the next few years. Advances in ultrasound technology permit high resolution imaging for detailed visualization of anatomy and pathology of the musculoskeletal system, including tendons, muscles, ligaments and fluid.…”
Section: Novel Imaging Modalitiesmentioning
confidence: 99%
“…MSKUS examination with sonopalpation is able to distinguish complex bloody from simple serous effusions with high accuracy as confirmed by needle aspiration. 25, 35 In addition, power Doppler permits rapid and dynamic assessment of synovial blood flow, thereby demarcating synovitis from fluid. In contrast, conventional MRI cannot easily differentiate joint fluid from synovitis without contrast administration, 36 nor can it easily distinguish bloody from non-bloody effusions (Figure 2).…”
Section: Novel Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Von Drygalski's research shows that only one-third of painful episodes reported by people with haemophilia are associated with bleeding into the joint 1 . Similarly, physicians find it hard to determine the cause of joint pain: in one small study 1 , von Drygalski and her colleagues found that physicians' assessments, based on patient interviews and physical examinations, were incorrect in 18 of 40 instances.…”
Section: Joint Inspectionmentioning
confidence: 99%